Avaliação dos efeitos da vagotomia total subdiafragmática e da gastrectomia vertical sobre a perda de peso corporal e a homeosotase glicêmica em camundongos obesos induzidos por dieta rica em lipídios - Felisberto Junior, Antonio Machado (2024)
In obesity, autonomic alterations such as vagal hyperactivity directly influence the regulation of energy and glycemic homeostasis, and total subdiaphragmatic vagal blockade results in significant weight loss in experimental models. Bariatric surgeries have proven highly effective in treating obesity; however, they are considered highly invasive procedures with significant post-surgical and physiological impacts. Therefore, understanding the mechanisms by which autonomic modulation via total vagal blockade inhibits the dysregulated afferent and efferent signals that emerge in obesity could provide an alternative to invasive surgical procedures such as vertical sleeve gastrectomy (SG). Thus, this study aimed to evaluate the effects of total subdiaphragmatic vagotomy and SG on body weight loss and glycemic homeostasis in diet-induced obese mice. For this purpose, male C57Bl/6J mice were fed a high-fat diet (HFD) containing 5.2 kcal/g (standard diet: 3.8 kcal/g). After eight weeks of HFD- induced obesity, mice were randomly assigned into subgroups based on the study’s methodological design and surgical intervention: Sham-operated, Total Subdiaphragmatic Vagotomy, and SG. After the interventions, mice continued on the HFD for an additional eight weeks. Subsequently, glucose and insulin tolerance tests were performed, followed by euthanasia and the collection of blood and tissue samples for biochemical, molecular, and histological analyses. All HFD-fed animals exhibited increased body weight, altered glycemic profiles, and insulin resistance. Mice subjected to total subdiaphragmatic vagotomy showed increased brown adipose tissue and perigonadal and retroperitoneal fat deposits, along with a significant reduction in plasma triglyceride and cholesterol levels. Additionally, these animals demonstrated significant improvement in hepatic steatosis compared to the sham-operated group. Similarly, SG led to greater body weight loss compared to other groups, as well as reductions in fasting glucose, insulin, and leptin levels. Thus, total subdiaphragmatic vagotomy performed after obesity induction altered white adipose tissue deposits, reduced hepatic steatosis severity, and improved glucose tolerance and insulin sensitivity in vagotomized mice. Furthermore, SG reduced food intake and total calorie consumption without affecting the expression of anorexigenic and orexigenic genes.